Problem Based Islamic Education Module Validated For Classroom Use: Modul Pendidikan Islam Berbasis Masalah Layak Digunakan Di Kelas - Zakiah, Fauzana; Halimah, Siti; Haidir, Haidir (Academia Open, 2026)
General Background: Islamic Religious Education requires contextual learning materials that connect religious concepts with students’ real-life social and digital experiences. Specific Background: Initial classroom conditions showed teacher-centered instruction, limited student discussion, weak analytical exploration, and insufficient development of balanced wasathiyah attitudes. Knowledge Gap: Existing teaching materials remained text-oriented and did not provide adequate problem-based exploration to support critical thinking and moderate religious attitudes. Aims: This study developed Problem Based Instruction Islamic Religious Education teaching materials to strengthen students’ critical thinking and wasathiyah abilities. Results: The developed module was designed through needs analysis, product design, development, validation, field testing, and revision. It integrated learning objectives, triggering questions, problem-based activities, reflection, worksheets, and assessment tools covering knowledge, attitudes, and skills. Expert validation indicated that the module met feasibility standards in content, language, and instructional design. Field testing involving 36 grade X software engineering students showed a positive student response score of 76.6%. Students became more active in discussion, more willing to express opinions, better able to draw group conclusions, and more open to different viewpoints. The module also supported logical reasoning, problem analysis, decision-making, tolerance, fairness, balance, and respectful interaction in social and digital contexts. Novelty: The study presents a contextual Islamic Religious Education module that combines problem-based learning, critical thinking indicators, and wasathiyah values within students’ everyday realities. Implications: The module can serve as an alternative teaching resource for more interactive, targeted, and character-oriented Islamic Religious Education learning. Highlights• Expert validation confirmed the module’s feasibility across content, language, and design.• Student responses reached 76.6% after classroom implementation.• Learners showed stronger discussion participation, logical reasoning, tolerance, and balance. KeywordsIslamic Religious Education; Problem Based Learning; Critical Thinking; Wasathiyah; Teaching Materials